The healing of Natalie Curtis [large type] - Kirkpatrick, Jane, 1946- (Center Point Large Print, 2021)
"Classically trained pianist and singer Natalie Curtis isolated herself for five years after a breakdown just before she was to debut with the New York Philharmonic. Guilt-ridden and songless, Natalie can't seem to recapture the joy music once brought her. In 1902, her brother invites her to join him in the West to search for healing. What she finds are songs she'd never before encountered - the haunting melodies, rhythms, and stories of Native Americans. But their music is under attack. The US government's Code of Offenses prohibits America's indigenous people from singing, dancing, or speaking their own languages as the powers that be insist on assimilation. Natalie makes it her mission not only to document these songs before they disappear but to appeal to President Teddy Roosevelt himself, who is the only man with the power to repeal the unjust law. Will she succeed and step into a new song... and a new future?"--